The Potential of Proteomic Approaches in Analyzing Protein Changes in Fermented Fishery Products - Nashwa Aqillah Yvonne Ramadhani; Muhammad Alfid Kurnianto; Anugerah Dany Priyanto (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Fermented fishery products are traditional foods widely produced across various regions and undergo complex biochemical changes during processing. One of the main changes determining product quality in proteolysis, the process of protein degradation into peptides, free amino acids, and other nitrogenous compounds that contribute to the development of flavor, aroma, texture, and food safety. Until now, the evaluation of protein changes in fermented fishery products has been dominated by conventional approaches such as total protein analysis, amino acid profiling, and soluble nitrogen parameters, which only capture the final outcome of proteolytic processing. This review aims to examine the potential of proteomic approaches in understanding protein transformation during the fermentation of fishery products. The findings indicate that liquid chromatography-tandem mass spectrometry (LC-MS/MS) base proteomic approaches are capable of comprehensively identifying and quantifying proteins and peptides, including changes in their abundance during fermentation. The integration of proteomic data with bioinformatics analysis has the potential to elucidate the relationships among microbial activity, protein transformation, and the development of product quality characteristics. Therefore, proteomics has the potential to become an important approach for advancing research on fishery fermentation at the molecular level. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 3: Good HealthSDG 9: Industry, Innovation and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 14: Life Below Water